EFFECTIVENESS OF CONSUMER PROTECTION LAW ENFORCEMENT FOR UNSAFE PRODUCTS CIRCULATING IN INDONESIA - Bernadetta Tjandra Wulandari; Irman Syahriar (SOSIOEDUKASI, 2026)
This study examines the effectiveness of consumer protection law enforcement against unsafe products circulating in Indonesia. The issue is important because unsafe products—including food, cosmetics, electronics, toys, and goods sold through digital marketplaces—continue to threaten consumer health, safety, and legal certainty despite the existence of consumer protection regulations. The research aims to analyze the legal framework, supervision and enforcement mechanisms, and the main barriers affecting the practical effectiveness of consumer protection law. This study employed a qualitative literature review approach using secondary data derived from legislation, books, journal articles, government reports, and institutional publications. The collected data were analyzed descriptively and analytically by identifying major themes related to product safety, law enforcement, market surveillance, and implementation challenges. The findings show that Indonesia already has a relatively comprehensive legal and institutional framework; however, its enforcement remains only partially effective. Persistent problems include fragmented regulations, limited institutional capacity, weak inter-agency coordination, low business compliance, and consumers’ weak bargaining position, especially in digital markets. Therefore, law enforcement remains more reactive than preventive in protecting consumers from unsafe products.